Extensive analysis of the cultivated medicinal herbal drug Origanum dictamnus L. and antimicrobial activity of its constituents. (April 2023) - Paloukopoulou, Charikleia; Tsadila, Christina; Govari, Sofia; Soulioti, Athina; Mossialos, Dimitris; Karioti, Anastasia
Abstract: Phytochemical investigations of the methanol extract from Origanum dictamnus L. (Lamiaceae) resulted in the isolation of forty compounds belonging to the classes of terpenes, resorcinol derivatives, flavonoids, depsides, neolignans and jasmonates. Chromatographic isolations were targeted by using two analytical platforms, NMR and HPLC-PDA-MS. In parallel, HPLC-PDA-MS of individual fractions enabled the unambiguous identification of additionally eight components. In total 48 constituents were isolated/identified. Among the isolated constituents are four undescribed compounds, one resorcinol derivative, one monoterpene, one diterpene and one acylated flavonoid glycoside. The structures of the isolated compounds were elucidated on the basis of spectroscopic analyses, including 1D and 2D NMR, and HPLC-ESI-MS and HRMS experiments. Representative compounds were tested for their antimicrobial activity against Staphylococcus aureus and Pseudomonas aeruginosa. I4-II7-dicarvacrol was the most potent constituent. Graphical abstract: Image 1 Highlights: 48 compounds were isolated/identified from the methanolic extract of Origanum dictamnus . Four undescribed compounds were identified. It is the second time that an abietane diterpenoid is isolated in Origanum sp. The structures of the undescribed compounds were determined by NMR and HR-MS. I4-II7-dicarvacrol was particularly effective against S. aureus .